2001
DOI: 10.13031/2013.6449
|View full text |Cite
|
Sign up to set email alerts
|

BMP Impacts on Sediment and Nutrient Yields From an Agricultural Watershed in the Coastal Plain Region

Abstract: The goal of the Nomini Creek watershed monitoring study was to quantify the effectiveness of BMPs at the watershed scale and to determine if the improvements in water quality could be sustained over a long-term period. Information on the long-term effectiveness of BMPs is critical since BMPs are being implemented under the state cost-share program to reduce nonpoint source pollution (NPS) to the Chesapeake Bay. The Nomini Creek project started in 1985 and was completed in 1997. A pre-versus post-BMP design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…It is important to note that the rates of erosion observed in the current study, although substantial, were not uncharacteristic for coastal plain soils in the region. Elsewhere, Inamdar et al (2001) reported annual erosion rates of only 0.9-1.1 Mg ha −1 from a row-cropped watershed on the coastal plain of Virginia.…”
Section: K N Johnson Et Almentioning
confidence: 99%
“…It is important to note that the rates of erosion observed in the current study, although substantial, were not uncharacteristic for coastal plain soils in the region. Elsewhere, Inamdar et al (2001) reported annual erosion rates of only 0.9-1.1 Mg ha −1 from a row-cropped watershed on the coastal plain of Virginia.…”
Section: K N Johnson Et Almentioning
confidence: 99%
“…Vegetative Filter Strip (VFS) is one of most effective BMPs to reduce sediment load and pollutants from agricultural fields [3][4][5][6][7][8]. VFS is usually installed at the edge of agricultural areas or the areas along streams, and it is designed to remove not only sediment load but also other pollutants, such as nutrients from runoff by filtration, infiltration, adsorption, absorption, deposition, decomposition, and plant uptake [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies, however, have only measured the effectiveness of specific project types at small scales (e.g. Sheiffield et al, 1997;Cey et al, 1999;Weigel et al, 2000) and only a few have measured the aggregated effectiveness of a variety of project types at a watershed scale (Cook et al, 1996;Edwards et al, 1996;Inamdar et al, 2001;Inamdar et al 2002). These watershed scale studies have generally been conducted on a single watershed.…”
Section: Introductionmentioning
confidence: 99%